ANALISIS DETERMINAN INTERNAL DAN EKSTERNAL YANG MEMENGARUHI BANK CAPITALIZATION RATIO PADA BANK SYARIAH DI INDONESIA - Iqbal, Muhammad (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2024)
This study aims to analyze the internal and external determinants influencing the Bank Capitalization Ratio (BCR) in Islamic banks in Indonesia. The variables examined include Non-Performing Financing (NPF), Return on Assets (ROA), Financing to Deposit Ratio (FDR), and inflation, using secondary data from annual reports of Islamic banks registered with the Indonesian Financial Services Authority (OJK) from 2018 to 2022. A multiple linear regression analysis reveals significant negative effects of NPF and inflation on BCR, while ROA shows a significant positive effect. However, FDR does not have a statistically significant impact. These findings suggest that managing credit quality (NPF), financial performance (ROA), and macroeconomic conditions (inflation) are critical to maintaining strong bank capitalization. The results provide important insights for policymakers and banking practitioners to strengthen risk management and ensure the stability of Islamic banking in Indonesia.